Cu-mediated vs. Cu-free selective borylation of aryl alkyl sulfones. Issue 3 (13th December 2021) - Huang, Mingming; Tang, Man; Hu, Jiefeng; Westcott, Stephen A.; Radius, Udo; Marder, Todd B.
Abstract : Borylation of cyclic aryl–alkyl sulfones gives boronate esters by selective cleavage of C(sp 2 )–SO2 or C(sp 3 )–SO2 bonds via Cu-mediated or Cu-free processes. Abstract : A Cu-catalysed borylation of aryl alkyl sulfones was developed for the high yield synthesis of versatile arylboronic esters using a readily prepared NHC–Cu catalyst. In addition, the selective cleavage of either alkyl(C)–sulfonyl or aryl(C)–sulfonyl bonds of a cyclic sulfone via Cu-free or Cu-mediated processes generates the corresponding sulfinate salts, which can be further derivatised to provide sulfonyl-containing boronate esters, such as sulfones and sulfonyl fluorides.